The rape of Lucretia and the founding of republics: readings in Livy, Machiavelli, and Rousseau - Matthes, Melissa M. (Penn State University Press, 2001)
Front Cover -- Copyright -- Contents -- Acknowledgments -- 1 A Conversation Between Republicanism and Feminism -- 2 Livy and the Repetition of Republican Foundations -- 3 La Mandragola and the Seduction of Lucrezia -- 4 The Seriously Comedic, or Why Machiavelli's Lucrezia Is Not Livy's Virtuous Roman -- 5 The Paradox of Rousseau's Politics and the Return to the Founding -- 6 Nouvelle Héloïse and the Supplement of Sexual Difference -- 7 Concluding Remarks -- Bibliography -- Index -- Back Cover.